Risk factors for musculoskeletal injury in preprofessional dancers: a systematic review - Kenny, Sarah J; Whittaker, Jackie L; Emery, Carolyn A (British journal of sports medicine, 2016)
BackgroundPreprofessional dancers partake in rigorous training and have high injury prevalence. Attempts to identify risk factors for dance injuries have focused on a diversity of intrinsic and extrinsic factors.ObjectiveTo identify and evaluate the evidence examining risk factors for musculoskeletal injury in preprofessional ballet and modern dancers.MethodsFifteen electronic databases were systematically searched to October 2015. Studies selected met a priori inclusion criteria and investigated musculoskeletal injury risk factors in preprofessional (elite adolescent, student, young adult) ballet and modern dancers. Two reviewers independently assessed the quality and level of evidence using the Downs and Black (DB) criteria and a modified Oxford Centre of Evidence-Based Medicine 2009 model, respectively.ResultsOf 1364 potentially relevant studies, 47 were included and scored. Inconsistent injury definition and methodology precluded meta-analysis. The most common modifiable risk factors investigated were anthropometrics (ie, body mass index, adiposity), joint range of motion (ie, lower extremity), dance exposure (ie, years training, exposure hours) and age. The median DB score across studies was 8/33 (range 2–16). The majority of studies were classified as level 3 evidence and few considered risk factor inter-relationships. There is some level 2 evidence that previous injury and poor psychological coping skills are associated with increased injury risk.ConclusionsBecause of the lack of high-quality studies, consensus regarding risk factors for musculoskeletal injury in preprofessional dancers remains difficult. There is a need for injury definition consensus and high-quality prospective studies examining the multifactorial relationship between risk factors and injury in preprofessional dance.